Detection of SARS-CoV-2 and other human enteric viruses in wastewater from Gothenburg - Norder, Helene; Nyström, Kristina; Patzi Churqui, Marianela; Tunovic, Timur; Wang, Hao; Saguti, Fredy; Enache, Lucica (University of Gothenburg, 2023)
The dataset is part of a research study lead by adjunct professor Heléne Norder and colleagues at Gothenburg University and the Clinical Microbiology Laboratory at Sahlgrenska University Hospital and at the Gryaab wastewater treatment plant in Gothenburg.

The first collection of weekly wastewater samples from the Gryaab wastewater treatment plant was between January and June 2013, the second was carried out throughout 2017, and the third started in February 2020 and is still ongoing, with a few weeks break between November 2022 and January 2023.

Gryaab receives wastewater from a population of approximately 790,000 inhabitants in Gothenburg and surrounding municipalities such as Ale, Härryda, Kungälv, Lerum, Mölndal and Partille as well as from industries and rain and stormwater from the older parts of the city.

Since the flow of wastewater varies greatly depending on rainfall or snowmelt, the volumes of the weekly wastewater samples to be analyzed for viruses are flow-weighted and vary in volume between 1L and 15L. The reason for flow-weighted samples is to ensure that the same amount of wastewater from each household is analyzed each week. Several sensitive in-house techniques have been developed to concentrate viruses in such large sample volumes. The first technique we developed involved the precipitation of viruses in wastewater with powdered milk (Hellmér et al., 2014). This technique was not suitable for detecting viruses in drinking water, because for this we needed to analyze several hundred liters of water. Therefore, we developed another technique that binds the virus to a membrane (Wang et al., 2020a), through which very large volumes of water can pass. This technique was later also used to concentrate viruses in incoming and treated wastewater (Wang et al 2020b). This latter technique was also found to be sensitive for detecting SARS-CoV-2 (Saguti et al., 2020). Because these techniques are labor-intensive and technically demanding, a new concentration technique was developed in the laboratory based on Ultrafiltration. The new technique provides higher sensitivity for detecting and recovering viruses, and also has a shorter processing time.

Nucleic acids were extracted from 1 ml of concentrate and RT-qPCR technique or qPCR is used (depending on the nucleic acid of the virus to be detected, RNA or DNA) for detection and quantification of the virus. Primers used to detect the different viruses can be found in Hellmér et al. 2014, Wang et al., 2020b and Saguti et al., 2022. The viruses now routinely investigated are SARS-CoV-2, Pepper Mild Mottle virus (PMMoV), norovirus GG2 (winter vomiting virus), sapovirus, enterovirus, astrovirus and adenovirus. More viruses will be added as new technologies are developed or if an outbreak caused by another virus is imminent. We type all viruses that increase in abundance in wastewater by sequencing, as we did for SARS-CoV-2 during the pandemic.

Metagenomics is also used to investigate the presence and spread of viruses that cause disease in humans or animals but are not diagnosed. Several viruses that cause gastroenteritis and can cause neurological complications have already been identified, some of which are now included in routine diagnostics at the Clinical Microbiology Laboratory. For the other viruses, the technology for detection has been developed and can be used if there are smaller or larger outbreaks that are not caused by the commonly diagnosed viruses.

The results from the weekly detection and quantification of SARS-CoV-2 and other enteric viruses are given from February 2020. The results from the detection and quantification of the other viruses are given from the sampling that started on week 20, 2023.

For more information see Amount of SARS-CoV-2 in wastewater (GU) | The Swedish Pathogens Portal (scilifelab.se) (https://pathogens-dev2.dckube3.scilifelab.se/dashboards/wastewater/covid_quantification/covid_quant_gu/) . The datasets are updated weekly.

The dataset is available as part of the Environmental Virus Profiling data section "The amount of SARS-CoV-2 virus in wastewater from Gothenburg" and on the data section for the other viruses on the Swedish Pathogens Portal.  (https://pathogens-dev2.dckube3.scilifelab.se)
Keywords: Public health not elsewhere classified; Environmental epidemiology; Medical and Health Sciences; Medicin och hälsovetenskap; Health Sciences; Hälsovetenskap